TOBACCO ISSUES AND THE 104TH CONGRESS. (Tufts Archival Research Center, 2007)
Report outlining the issues related to tobacco facing the 104th Congress. Summarizes the position of the tobacco industry on several issues such as: excise taxes and their regressive nature, smoking bans, youth smoking and fire safe cigarettes among others. Focuses on the unfair attacks and taxes levied against the tobacco industry.